Philippine medical thesaurus on anatomy body regions in Kapampangan - Lising, Jeffrey O.; Castillo, Africa R. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2004)
Effective care and management of a patient is attained with good patient doctor relationship. Proper management comes with proper diagnosis. Diseases are often misdiagnosed because of miscommunication due to language differences between the doctor and the patient. Communication barrier between them has been one of the major constraints in better disease management. However, there are no books currently available to translate standard medical terms into Filipino or other Philippine dialects.
The Multilingual Philippine Medical Thesaurus is a part of collaborative effort of the Institute of Library and Information Science, University of the Philippines, Diliman and the Medical Informatics Unit, College of Medicine, University of the Philippines Manila. Its main purpose is to produce a tool to aid the Filipino users and, therefore, lessen the difficulty and confusion in medical terminologies employed in the country.
This paper focused on body regions subcategory of the 17 subcategories of 'Anatomy'. The terms were gathered from the Medical Subject Headings (MeSH) and were translated into Kapampangan with the use of Kapampangan dictionaries that were ranked by experts according to authoritativeness. Interviews with medical and non-medical professionals were done to determine the validity of the translated terms. The thesaurus making was based on the ISO 5964, which is a standard guideline for multilingual thesaurus construction.
Out of the seventy-four (74) downloaded terms, this researcher was able to translate fifty-nine (59) terms using the dictionaries ranked by experts, fifteen (15) were not translated and thirteen (14), from the fifteen with no translation, had Scope notes. The completion of this paper will help not only to promote language consistency in the medical subject area, but also this will somehow preserve a part of Kapampangan language and culture.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings -- Medicine -- Philippines -- Pampanga; Body, Humans; Pampanga language -- Medical Pampanga